Mental health of older adults in humanitarian settings in low- and middle-income countries: a retrospective analysis from Médecins sans Frontières-supported mental health services, 2019–2024 - Joyce L Browne; Grazia Caleo; Patrick Keating; Oscar Franco; Elburg van Boetzelaer; Nicole Wasara; Erickmar Rodriguez; Favila Escobio; Umberto Pellecchia; Judith van de Kamp; Martins Dada; Nadia Fredj; et al. (BMJ Global Health, 2025)
Background More complex humanitarian emergencies have a profound impact on a rapidly growing ageing population. There are few data available on the mental health conditions of older people in humanitarian settings. This study describes mental health symptoms among older adults to inform the development of age-adapted and gender-adapted mental health services in humanitarian contexts.Methods This multicountry study includes data from adults aged 50 years or older that accessed Médecins sans Frontières-supported mental health services in humanitarian settings across 20 countries between July 2019 and July 2024. Mental health symptoms and precipitating events were compared by age, sex and displacement status using regression analyses. Analyses were mutually adjusted for sex and displacement status to account for confounding.Findings Data of 21 926 adults were included. Older adults presented at mental health services with anxiety-related symptoms (36%), physical complaints (33%) and mood-related symptoms (18%). Compared with men, women had higher odds of reporting mood-related symptoms (adjusted Odds R=1.60; 95% CI 1.48 to 1.73), and precipitating events related to sexual trauma or abuse (aOR=9.98; 95% CI 8.11 to 12.40). Compared with non-displaced older adults, displaced older adults had higher odds of reporting neuro-psychiatric-related (aOR=2.35; 95% CI 2.07 to 2.66), mood-related (aOR=2.08; 95% CI 1.93 to 2.24), ageing-related (aOR=1.47; 95% CI 1.15 to 1.86) and anxiety-related (aOR=1.42; 95% CI 1.33 to 1.51) symptoms, and precipitating events related to sexual trauma or abuse, abuse during detention and violence, with variations depending on sex.Interpretation Older adults in humanitarian settings experience diverse mental health symptoms, with critical differences by sex and displacement status. Women were more likely than men to present with mood-related symptoms and to report experiences of sexual trauma and abuse. Displacement significantly heightens exposure to violence and mental health presentations for both women and men. These findings underscore the urgent need to strengthen protection systems and ensure access to gender-sensitive mental health interventions for older populations.